History of the Kabat-Meneng Banyuwangi Railroad Line from 1985 to 2001 - Ghoziyah Ilza Rona Afcarina; Akhmad Ryan Pratama; Sumarjono Sumarjono; Kayan Swastika; Mohamad Na’im; Robit Nurul Jamil; Gusti Ngurah Ary Kesuma Puja (JURNAL HISTORICA, 2023)
This study discusses the construction process of the Kabat-Meneng Banyuwangi railway line in 1985-2001. The main problem of this study is how is the background and process of the construction of the Kabat-Meneng Banyuwangi railway line?The problem is discussed through an in-depth study of the railway construction process based on written and oral sources. In this study, most sources come from newspaper archives, reports of the central statistics agency, and archives. The method used is the historical research method, which has five steps of research: topic selection, source collection, verification, interpretation, and writing.The conclusion that can be drawn from this study is that the construction of the Kabat-Meneng railway line is a long process motivated by the interests of fertilizer distribution in the Banyuwangi area. In addition, the transportation of export and import commodities to the port of Banyuwangi is getting smoother so that many industries also use train services. Trains not only play a role in passenger transportation, but also play a role in the transportation of large quantities of goods. So this is what makes the train a popular transportation for the community. The construction of railroad lines and infrastructure is not just built immediately. But there is a purpose for building a railroad line. Especially in Banyuwangi, the Kabat-Meneng railway line was built because there is a need for transportation for the transportation of fertilizers which will be channeled to the port of Banyuwangi for export. Kata Kunci: Railroad, Kabat, Meneng, Banyuwangi